The Jurisprudential Rule of Expediency in the Laws and Regulations of Adoption and Children Without Guardians - Abdolhamid Talebi (آموزه‌‌های فقه مدني, 2023)
Islamic jurisprudence is not indifferent to children without guardians or bad parenting children (children without adequate parental care) and has placed their affairs as a collective duty (an act which is rested on Muslims till it is done by some of them alternatively) to the direct affinity of children, judge and Muslims, and has prevented the expansion of the rulings on the natural relationship between parents and adopted children, and its challenges have not been ineffective in the relevant laws in Islamic countries. It is important to notice what is the way out of this problem in Islamic jurisprudence? This article has been compiled using library studies and descriptive-analytical method and has studied this challenge while criticizing Iran’s statute laws by adhering to the jurisprudential Rule of Expediency and expressed the solutions. The findings of this article based on Quranic and narrative principles, conditional and limited adoption in Islamic jurisprudence using the element of expediency as the basis of Sharia rulings and the philosophy of the enactment of rules are in all decisions that his/her guardians, whether judge or godfather make and preserving the child’s true lineage, the necessity of alimony and custody in order to preserve his life and preserve the child’s financial rights (inheritance) and observe the religious blood relations within the prohibited degrees of marriage in the family are also emphasized and the decision is subject to the observance of expediency with the aim of the growth and excellence of bad parenting children in addition to children without guardians in many cases.